2009
DOI: 10.1051/apido/2009049
|View full text |Cite
|
Sign up to set email alerts
|

Small-cell comb foundation does not impede Varroa mite population growth in honey bee colonies

Abstract: -In three independently replicated field studies, we compared biometrics of Varroa mite and honey bee populations in bee colonies housed on one of two brood cell types: small-cell (4.9 ± 0.08 mm cell width, walls inclusive) or conventional-cell (5.3 ± 0.04). In one of the studies, ending colony bee population was significantly higher in small-cell colonies (14994 ± 2494 bees) than conventional-cell (5653 ± 1082). However, small-cell colonies were significantly higher for mite population in brood (359.7 ± 87.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 7 publications
4
18
1
1
Order By: Relevance
“…On the contrary, we found that the mean mite counts started out the same for the two groups of colonies and remained indistinguishable over the next 4 months. We conclude that the small-cell treatment did not hamper the growth of the populations of Varroa mites in our study colonies in the northeastern USA (NY state), a conclusion that echoes those of two analogous studies conducted in the southeastern USA (Florida and Georgia) (Ellis et al 2009;Berry et al 2010) and one study conducted in Ireland that examined mite reproduction in small-cell (4.91 mm) and standard-cell (5.38 mm) combs (Coffey et al 2010).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…On the contrary, we found that the mean mite counts started out the same for the two groups of colonies and remained indistinguishable over the next 4 months. We conclude that the small-cell treatment did not hamper the growth of the populations of Varroa mites in our study colonies in the northeastern USA (NY state), a conclusion that echoes those of two analogous studies conducted in the southeastern USA (Florida and Georgia) (Ellis et al 2009;Berry et al 2010) and one study conducted in Ireland that examined mite reproduction in small-cell (4.91 mm) and standard-cell (5.38 mm) combs (Coffey et al 2010).…”
Section: Discussionsupporting
confidence: 85%
“…It now seems highly doubtful, however, that when workers of the European races of A. mellifera are reared in small cells (4.8 mm, this study; or 4.9 mm, Ellis et al 2009, Berry et al 2010, Coffey et al 2010, the fill factor is high enough to inhibit mite reproduction and so achieve mite control. We measured the fill factor (the ratio of thorax width to cell width, expressed as a percentage) for both the standard-cell combs and the small-cell combs in our study.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Alguns estudos mostram que a infestação pela Varroa destroctor é duas vezes maior em ninhadas de células grandes do que em ninhadas de células pequenas. Sendo assim, este fato se mostra como um dos responsáveis pela maior suscetibilidade das abelhas europeias em relação as abelhas africanizadas, uma vez que suas células de cria são maiores (Message & Gonçalves, 1995;Berry et al, 2010). A infestação do ácaro pode variar de forma diferente entre as estações do ano, quando efeitos, tais como a disponibilidade de alimentos, mudanças de comportamento e interações com outros patógenos, influenciarão na taxa de lotação desse parasita (Pinto et al, 2015).…”
Section: Varrooseunclassified
“…It may also increase instances of entrapment, where the mite is pinned between the brood cell wall and the silk cocoon spun by the pupating larvae, effectively immobilizing and ultimately killing the foundress, preventing reproduction entirely. As a natural trait, a smaller cell size has been found in the surviving African and Africanized A. mellifera populations; however, as a mechanical method of controlling V. destructor managed by European beekeepers, evidence has been mixed, with studies supporting (De Jong and Morse 1988;De Ruijter and Calis 1988;Message and Gonçalves 1995;Piccirillo and De Jong 2003;Maggi et al 2010) and refuting the effect (Ellis et al 2009;Taylor et al 2008;Berry et al 2009). Aside from this ambiguity, interactions with other surviving mechanisms have not yet been thoroughly investigated: Small cell size can increase honeybee responsiveness to certain hygienic tests, such as the example provided by Olszewski et al (2014); bees on small cell size tended to remove pin-killed brood faster than bees on a larger cell size Though known surviving African/ized populations have a smaller cell size, the role small cell size plays in populations of naturally-surviving European honeybees is currently not known.…”
Section: Introductionmentioning
confidence: 99%